2009
DOI: 10.1002/btpr.290
|View full text |Cite
|
Sign up to set email alerts
|

Rapid media transition: An experimental approach for steady state analysis of metabolic pathways

Abstract: Commonly steady state analysis of microbial metabolism is performed under well defined physiological conditions in continuous cultures with fixed external rates. However, most industrial bioprocesses are operated in fed-batch mode under non-stationary conditions, which cannot be realized in chemostat cultures. A novel experimental setup-rapid media transition-enables steady state perturbation of metabolism on a time scale of several minutes in parallel to operating bioprocesses. For this purpose, cells are sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…This was demonstrated by comparing Flux Variability Analysis of the knock‐out mutants and the reference strain. The deletion of the malic enzymes thus ensured certainty in flux estimation and therefore enables further characterization of the L‐phenylalanine production by combination of theoretical (e.g., metabolic control analysis, Hatzimanikatis and Bailey, ) and experimental approaches (e.g., Rapid media transition, Link et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was demonstrated by comparing Flux Variability Analysis of the knock‐out mutants and the reference strain. The deletion of the malic enzymes thus ensured certainty in flux estimation and therefore enables further characterization of the L‐phenylalanine production by combination of theoretical (e.g., metabolic control analysis, Hatzimanikatis and Bailey, ) and experimental approaches (e.g., Rapid media transition, Link et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another option is making use of constraint based approaches during controlled substrate limited fed‐batch processes where extracellular fluxome [e.g., biomass formation (Link et al, )] is kept constant. Link et al () demonstrated that a constant growth rate in fed‐batch mode provided metabolic steady state. Therefore, constraint based approaches are applicable for fed‐batch processes and chemostat cultures are not necessarily essential for steady state assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…Perturbation methods are divided into dynamic approaches (Chassagnole et al, ; Heijnen and Verheijen, ; Magnus et al, ; Taymaz‐Nikerel et al, ) and steady‐state approaches (Link et al, ; Nasution et al, ). Perturbation experiments often apply techniques for metabolic analyses of cells sampled from a continuing process, to avoid any process disturbance and to repeat the perturbation experiments at several process times (Link et al, ; Taymaz‐Nikerel et al, ). Perturbation experiments may be performed with culture broth samples, which are pumped through a specially designed plug‐flow reactor (De Mey et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, samples are rapidly centrifuged and the biomass is transferred into small‐scale stirred tank reactors. These contain fresh media with varying carbon sources to allow the measurement of metabolome and fluxome data during short‐term (<20 min) batch experiments (Link et al, ). The proteome of the cells is assumed to remain unchanged in both cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation